The possible modulation of p63 and other genes in prostate tumorigenesis - Su, Nguok Ngie (Universiti Malaysia Sarawak (UNIMAS), 2007)
Prostate cancer (PCa) affects males in Malaysia, where in Peninsular Malaysia prostate cancer was the sixth most frequent cancer in males and accounted for 6.4% of the total cancers in males for the year 2003. In Sarawak, prostate cancer ranked eighth among the most frequent cancer occurrence in males with a rate of 3.4% of the total cancers in males for the year 1996-2000. Mice knockout for p63 have exhibited developmental defects such as abnormal skin and absence of hair follicles, prostate, breast, teeth and mammary glands. Mutation of p63 in human resulted in the ectrodactyly, ectodermal dysplasia and facial clefts (EEC) syndrome. Mutational analyses have revealed heterozygous mutation of p63 in colon (DLD1) and ovarian (SKOV3) cancer cell lines. Studies have shown that the p63 gene was selectively expressed in basal cells of normal, benign prostatic hyperplasia (BPH), prostatic epithelial stem cells and preneoplastic prostatic tissue Although indirect evidences from literature have implicated possible role(s) of p63 in prostate cancer, its actual involvement in the carcinogenesis of this cancer has yet been established. Furthermore, few studies have been done so far to delineate the molecular and genetic mechanisms that pertain to the predisposition and progression of prostate cancer. In this study, mutation analysis of p63 on prostate cancer cell line (PC-3), PCa biopsy and BPH biopsies have been performed. However, no mutation was detected in PC-3, CaP and BPH biopsies. Expression studies on various isoforms of p63 were performed on normal human prostate tissue, PC-3, clinically local prostate cancer and benign prostatic hyperplasia using RT-PCR. In addition, we report new data on the identification of differentially expressed III